Hubungan Antara Kepemimpinan Instruksional Kepala Sekolah, Kompetensi Profesional Guru, Motivasi Erprestasi, dan Kinerja Guru SDN di Kecamatan Murung Pudak Kabupaten Tabalong - Fetty Dachliani Sukma; Aslamiah Aslamiah; Ahmad Suriansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to analyze the direct and indirect relationship between the principal's instructional leadership, professional competence, achievement motivation and the work discipline of SDN teachers in Murung Pudak District, Tabalong Regency. The method used is quantitative descriptive research using a correlational path analysis model to analyze relationship patterns between variables. The research population was 280 teachers from 24 elementary schools in Murung Pudak District and 143 respondents as research samples using the Proportionate Random Sampling technique and the proportional allocation formula. Data collection uses questionnaire instruments and data analysis uses descriptive analysis, classical assumption testing, hypothesis testing and path analysis. results of the analysis of the regression coefficient values for the principal's instructional leadership variable with teacher performance were 0.421, the professional competency variable with performance was 0.330, the achievement motivation variable with performance was 0.256, the principal's instructional leadership variable with achievement motivation was 0.485, the professional competency variable with achievement motivation was 0.485. 0.437, the principal's instructional leadership variable with performance through achievement motivation is 0.124 and the professional competency variable with performance through achievement motivation is 0.112. Conclusion of this research is that the principal's instructional leadership variables, professional competence, achievement motivation and performance of SDN teachers in Murung Pudak District, Tabalong Regency are all in the high category. Keywords:Instructional Leadership, Motivation, Professional Competence, Performance.